Defending Islam Action and Its Impact on the Local Islamic Conservatism Movement in West Sumatra - Zulfadli, Zulfadli (Universitas Islam Negeri Sunan Kalijaga, 2023)
The massive demonstrations as part of the Defending Islam Action against Ahok in 2016 have had a broad impact on the dynamics of contemporary Indonesian politics. The event has not only created socio-political polarization in society but also seeped into local political dynamics in West Sumatra. So far, most studies have focused on the motives and causal factors of the Islamic defense action with its various implications, but there are still few studies that explain the influence of this action on the local Islamic conservatism movement in West Sumatra. Specifically, this study answers the question of how the influence of the Defending Islam Action on the local Islamic conservatism movement in West Sumatra after the 212 rally. A deep understanding of the development of Islamic conservatism in the local context can develop theories of Islamic conservatism in explaining the Islamic revival movement in Indonesia. This research uses a qualitative method by interviewing a number of actors of the local Islamic conservatism movement in West Sumatra. The results of this study show that the transformation of national politics in the issues of the Defending Islam Action has a significant impact on the local Islamic conservatism movement. The national political factor not only affects the local Islamic conservatism movement but also the proliferation of such movements locally, that are active in responding to social, political and religious issues. The national political factor followed by local political decentralization is a political opportunity for local Islamic conservatism groups to carry out conservative Islamic agendas in West Sumatra.